The development of self-assessment accuracy in mathematical word problems: A study of primary school learners - Smetáčková, Irena; Páchová, Anna (Scientia in educatione, 2025)
Self-assessment, as a critical component of self-regulated learning, plays a significant role in improving learning achievement. This study focuses on the accuracy of self-assessment in the context of mathematical word problems among primary school students. The evolution of self-assessment accuracy was examined between the second and third grades. The impact of cognitive abilities, mathematical knowledge, and teacher evaluations was investigated. Data were collected from a sample of 542 primary school pupils. Our findings reveal that students demonstrated greater accuracy in self-assessing their performance in mathematical word problems in Year 2 compared to Year 3. This self-assessment accuracy varied based on cognitive abilities and the pedagogical environments. These findings suggest the importance of creating adequate classroom conditions to enhance self-assessment accuracy.